A Case of Giant Lipoma Causing Chronic Recurrent Intussusception of the Colon - Lee, Chang Seob (The Korean Society of Gastrointestinal Endoscopy, 2012)
Colonic lipomas, which often occur in elderly women, usually have small size and occur mainly in the cecum and ascending colon. Most colonic lipomas are asymptomatic and identified incidentally at the time of endoscopy or surgery. However, they may cause symptoms such as bleeding, obstruction or intussusception as their size increases. Intermittent episodes of intussusception are uncommon but may be caused by large pedunculated lipoma. In a 68-year-old woman suffering intermittent abdominal pain, 5.5×4.5×3.8-cm huge mass was found by colonoscopy at proximal ascending colon, which was intussuscepted to proximal transverse colon on abdominal computed tomography. Segmental right colonic resection was conducted. We report a case of symptomatic giant pedunculated colonic lipoma causing intussusception requiring surgical intervention, with a successful recovery after surgery.